Mesenchymal stromal cells for the treatment of Alzheimer’s disease: Strategies and limitations - Regmi, Shobha; Liu, Daniel Dan; Shen, Michelle; Kevadiya, Bhavesh D.; Ganguly, Abantika; Primavera, Rosita; Chetty, Shashank; Yarani, Reza; Thakor, Avnesh S. (Frontiers in Molecular Neuroscience, 2022)
Alzheimer’s disease (AD) is a major cause of age-related dementia and is characterized by progressive brain damage that gradually destroys memory and learning ability, which ultimately declines a patient’s ability to perform daily activities. Although some of the pharmacological treatments of AD are available for symptomatic relief but are not able to limit the progression of AD and have several side effects. Mesenchymal stem cells (MSCs) could be a potential therapeutic option in treating AD due to their immunomodulatory, anti-inflammatory, regenerative, antioxidant, anti-apoptotic, and neuroprotective effects. MSCs not only secret neuroprotective and anti-inflammatory factors to promote the survival of neurons but also transfer functional mitochondria and miRNAs to boost their bioenergetic properties for their efficient functions and improve microglial clearance of accumulated protein aggregates. This review focuses on different clinical and preclinical studies using MSC therapy for treating AD, their outcomes, limitations and the strategies to overcome for their clinical translation.